2013
DOI: 10.3357/asem.3262.2013
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Disease After Hip Replacement: Aeromedical Implications of Arthroprosthetic Cobaltism

Abstract: This case illustrates the potential for a hip prosthesis to occultly impair safe functioning of aviators. Based on this case and others, we suggest modifications to aeromedical policy relating to waiver requests after hip replacement, including routine monitoring of serum cobalt and chromium levels in recipients of metal-on-metal hip prostheses. The evaluation of aviators having an elevated cobalt level is also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 8 publications
(8 reference statements)
0
18
0
Order By: Relevance
“…Systemic cobaltism following MoM THA has been published in previous case reports and series [12] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] . A systematic review of 25 patients identified several organ systems involved with the cardiovascular system (60%) being the most frequently affected, followed by central nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic cobaltism following MoM THA has been published in previous case reports and series [12] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] . A systematic review of 25 patients identified several organ systems involved with the cardiovascular system (60%) being the most frequently affected, followed by central nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…CoNPs produced by the reduction or wear of internal plants are rst deposited around the internal xation plate and arti cial joint prosthesis to cause in ammatory pseudotumor around the implant, loosening of the prosthesis, as well as local osteoporosis. Meanwhile, due to their nano-size effect, CoNPs are more likely to enter into the blood and lymphatic system, followed by their broad distribution in multiple organs or tissues of the human body through systemic circulation, resulting in different adverse symptoms [4][5][6][8][9][10][11]. Therefore, the patients undergoing MOM joint replacement need to be monitored and detoxi ed.…”
Section: Introductionmentioning
confidence: 99%
“…Among these particles, cobalt nanoparticles (CoNPs) are the most abundant ones with the highest toxicity [1,2], which could cause early failure of arti cial joints [3]. Tower et al well demonstrated the multiple systemic adverse reactions after metal-on-metal (MOM) joint replacement and named the disease as arthroprosthetic cobaltism syndrome (ACS) [4][5][6][7][8]. CoNPs produced by the reduction or wear of internal plants are rst deposited around the internal xation plate and arti cial joint prosthesis to cause in ammatory pseudotumor around the implant, loosening of the prosthesis, as well as local osteoporosis.…”
Section: Introductionmentioning
confidence: 99%